EXPLORING THE COLLEGE STUDENTS' READING SOURCE PREFERENCES AND THEIR PERCEIVED IMPACT ON VOCABULARY AND COMMUNICATION SKILLS - Adrallisman Adrallisman; Mahyati Mahyati; Zaenal Abidin; Eka Uliyanti Putri; Gunawan Gunawan (Universitas HKBP Nommensen, 2026)
Reading is considered elementary skill supporting the other language skill, such as writing, speaking, and listening. Despite the above importance, very few studies highlight the students’ perceptions regarding the writing activities. The research study examined the students’ perceptions on their reading activities. There were 40 active students, who were surveyed for this research. The research analyzed participants’ responses describing their view on their reading activities and the other relevant factors affecting their reading activities, such as the preferred reading sources, the reasons when reading a novel, and the ideal teacher in teaching reading. The findings revealed the students’ preference toward much shorter reading sources rather than the lengthy ones. The also stated that the preferred to read the news and relevant sources with their jobs/activities. Furthermore, they stated that the main reason for reading the novels was mainly due to the popularity of the novel. Lastly, it was revealed that reading activity was deemed important in improving both the students’ vocabulary and communicative capacity. They suggested that the lecturers be the ones who could help facilitating the reading activities.